Intravesical Foreign Body via a Vesicoperineal Fistula - Aaron M. Potretzke; Kelvin S. Wong; Tracy M. Downs (Case Reports in Urology)
Male urethral “play” has been described for centuries. There are serious potential complications in this. We present a bizarre case of a variant of such play. A 49-year-old man presented with abdominal pain and incontinence. He had created a “neovagina” at the perineum for self-pleasure. The handle of a toilet brush was placed in the neovagina for self-pleasure but retracted into the bladder via a vesicoperineal fistula. An open cystotomy was performed to remove the foreign body.